2017
DOI: 10.1021/jacs.7b09737
|View full text |Cite
|
Sign up to set email alerts
|

Hexagonally Ordered Arrays of α-Helical Bundles Formed from Peptide-Dendron Hybrids

Abstract: Combining monodisperse building blocks that have distinct folding properties serves as a modular strategy for controlling structural complexity in hierarchically organized materials. We combine an α-helical bundle-forming peptide with self-assembling dendrons to better control the arrangement of functional groups within cylindrical nanostructures. Site-specific grafting of dendrons to amino acid residues on the exterior of the α-helical bundle yields monodisperse macromolecules with programmable folding and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 87 publications
3
18
0
Order By: Relevance
“…We recently reported examples of α-helix bundle-forming peptide-dendron hybrids that self-organize in an hexagonally ordered array of columns. 54 We found that the helix bundle stoichiometry in the liquid crystalline mesophase matches the stoichiometry of the bundle formed by the peptide in aqueous buffer. This remarkable correspondence implies that folding and self-assembly instructions encoded by the amino acid sequence persist in the non-biological environment of the liquid crystalline mesophase.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…We recently reported examples of α-helix bundle-forming peptide-dendron hybrids that self-organize in an hexagonally ordered array of columns. 54 We found that the helix bundle stoichiometry in the liquid crystalline mesophase matches the stoichiometry of the bundle formed by the peptide in aqueous buffer. This remarkable correspondence implies that folding and self-assembly instructions encoded by the amino acid sequence persist in the non-biological environment of the liquid crystalline mesophase.…”
Section: Introductionmentioning
confidence: 61%
“…The same polar and non-polar residues were used in our previously reported α-helical bundle-forming peptide-dendron hybrids. 32, 33, 54, 55 The side-chain amino group of each lysine residue is efficiently acylated using dendritic pentafluorophenyl esters. 54 DeGrado and Lear have shown that a seven-residue peptide with alternating leucine and lysine residues self-assembles into a β-sheet structure in buffered aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations